Tingkat Pengetahuan Tentang Faktor Risiko Persalinan dengan Tingkat Kecemasan dalam Menghadapi Persalinan pada Ibu Hamil Trimester III di Puskesmas Sleman Yogyakarta - Anisa Nurlailiyah; Ircham Machfoedz; Desiana Pitta Sari (Alma Ata University Press, 2015)
According to the 2012 Demographic and Health Survey of Maternal Mortality Rate (MMR) the number were 359/100.000 of live births. In DIY, MMR 2013 recorded 204/100.000 live births. In Sleman MMR were 19 cases. Maternal mortality is influenced by many factors one of which is anxiety that can affect the condition of fetus or mother. Results of baseline study of 13 respondents, 6 respondents in good knowledge, 7 respondents in enough knowled. However, all respondents are experiencing anxiety. The purpose of this study was to determine the relationship between knowledge level of risk factors delivery and anxiety level of facing delivery in pregnant women trimester III at Puskesmas Sleman, Yogyakarta. This study was used analytical with cross sectional design. Subjects of study was 120 third trimester pregnant women who checkups at Puskesmas Sleman Yogyakarta on March 4 to June 4, 2015. Samples were obtained by accidental sampling which consisted of 42 respondents. Data analysis used Pearson Product Moment. Results showed that most of respondents aged 20-35 years were 35 people (83.3%), as a House Wife were 18 respondents (42.9%), the level of knowledge in fair categories were 32 respondents (76.2%), the level of anxiety in worried categories were 27 respondents (64.3%), bivariate analysis r=0.091 and p-value=0.566. In conclusion, there was no significant relationship between knowledge level of risk factors delivery and anxiety level of facing delivery in the third trimester pregnant women in the health center in Yogyakarta Sleman.